Language Maintenance of the Dialect Bali Aga Cempaga: A Sociolinguistic Study and its Implications for Language Revitalisation - Ni Ketut Veri Kusuma; Elsita Lisnawati Guntar; I Made Aryastawan (Journal of English Language and Education, 2026)
This study examines the maintenance of the Bali Aga dialect in Cempaga Village, Banjar District, Buleleng Regency, Bali. The Bali Aga dialect is an older form of the Balinese language spoken by the Bali Aga community (highland/indigenous Balinese), historically predating and linguistically distinct from the Lowland Balinese (Lowland Balinese) dialect. Cempaga Village, as one of the Bali Aga communities, harbors unique linguistic wealth, yet faces mounting pressures from modernization and language shift. This research aims to: (1) identify the distinctive linguistic features of the Cempaga Bali Aga dialect that differentiate it from the Lowland Balinese dialect; (2) analyze the social, economic, and cultural factors influencing dialect maintenance; and (3) formulate contextual and sustainable revitalization strategies. The study employs a descriptive-qualitative method with a linguistic ethnographic approach. Data were collected through in-depth interviews with 42 purposively selected informants, eight months of participant observation, and spontaneous speech recordings. Results indicate that the Cempaga Bali Aga dialect possesses 78 unique lexical items absent from the Lowland dialect, a distinct phonological system with 12 distinctive phonemes, and unique morphosyntactic patterns. Dialect maintenance is positively supported by communal identity, active customary ritual practices, and elderly generational awareness. Primary threats arise from Indonesian language dominance in formal education, inter-regional intermarriage, and the prevalence of Indonesian-Lowland Balinese digital media. This study recommends community-based revitalization programs that integrate the dialect into local curricula and digital platforms.